Experiences of school coexistence: importance of assertiveness: from Padrón to Catoira. (Journal of Parents and Teachers, 2014)
This article talks about passive or submissive people, who believe in not having rights and don’t defend their interests and opinions; and aggressive people who adopt a defiant and offensive behaviour. Therefore, this article suggests a program of assertiveness development with ten sessions per year during three years. This type of intervention arises spontaneous participation of students, their interest and motivation.
Keywords: Experiences; school coexistence; assertiveness; interpersonal relationship; social skills.